Software System Package Dependencies and Visualization of Internal Structure - Ahmad Abdul Qadir Alrababah (Institute of Advanced Engineering and Science, 2018)
This manuscript discusses the visualization methods of software systems architecture with composition of reverse engineering tools and restoration of software systems architecture. The visualization methods and analysis of dependencies in software packages are written in Java. To use this performance graphit needs to describe the relationships between classes inside the analyzed packages and between classes of different packages. In the manuscript also described the possibility of tools to provide the infrastructure for subsequent detection and error correction design in software systems and its refactoring.